2018
DOI: 10.3390/cancers10080257
|View full text |Cite
|
Sign up to set email alerts
|

Stereotactic Body Radiation Therapy for Patients with Pulmonary Interstitial Change: High Incidence of Fatal Radiation Pneumonitis in a Retrospective Multi-Institutional Study

Abstract: Pretreatment pulmonary interstitial change (PIC) has been indicated as a risk factor of severe radiation pneumonitis (RP) following stereotactic body radiation therapy (SBRT) for early-stage lung cancer, but details of its true effect remain unclear. This study aims to evaluate treatment outcomes of SBRT for stage I non-small cell lung cancer in patients with PIC. A total of 242 patients are included in this study (88% male). The median age is 77 years (range, 55–92 years). A total dose of 40–70 Gy is administ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 18 publications
0
32
1
Order By: Relevance
“…A retrospective analysis reported that V5 was significantly associated with the occurrence of RP grade progression after carbon-ion radiotherapy for NSCLC with ILD [ 28 ]. Onishi et al [ 29 ] found that a V20 ≥ 10% is a major risk factor for severe RP in stage I NSCLC patients with subclinical ILD. In the present study, no correlation was observed between the incidence of RP and V20.…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective analysis reported that V5 was significantly associated with the occurrence of RP grade progression after carbon-ion radiotherapy for NSCLC with ILD [ 28 ]. Onishi et al [ 29 ] found that a V20 ≥ 10% is a major risk factor for severe RP in stage I NSCLC patients with subclinical ILD. In the present study, no correlation was observed between the incidence of RP and V20.…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective analysis reported V5 was signi cantly associated with the occurrence of RP grade progression after Carbon-ion radiotherapy for NSCLC with interstitial lung disease [28]. In addition, Onishi et al [29] found that V20 ≥10% is a major risk factor for severe RP in stage I NSCLC patients with subclinical ILD. In the present study, no correlation was observed between the incidence of RP and V20.…”
Section: Discussionmentioning
confidence: 99%
“…When severe ILD is present, radiotherapy for inoperable LC is contraindicated because it causes radiation pneumonitis in up to 43% of patients [39]. Subclinical ILD is also considered a radiation-pneumonitis risk factor with some attributable fatalities, hence, the indication of radiotherapy, even stereotactic, should be decided by carefully considering the risks and benefits for ILD patients [40]. In our cohort, eight LC-ILD patients underwent radiotherapy: two (25%) developed non-severe radiation pneumonitis, statistically comparable to LC-noILD (12%) patients (see Supplementary Table S4).…”
Section: Discussionmentioning
confidence: 99%